2020
DOI: 10.1177/1120672120926859
|View full text |Cite
|
Sign up to set email alerts
|

Structural assessment of the optic nerve in patients with obstructive sleep apnea syndrome: Case–control study

Abstract: Objective Obstructive sleep apnea syndrome has been identified as a possible risk factor for optic nerve pathology such as glaucoma, nonarteritic ischemic optic neuropathy, and optic disk edema. Accordingly, we aimed to evaluate structural changes of the apparently normal optic nerve in obstructive sleep apnea syndrome patients with effects of its severity. Materials and methods In this prospective case–control study, 47 eyes of 47 obstructive sleep apnea syndrome patients diagnosed with polysomnography and 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 28 publications
0
10
1
Order By: Relevance
“…Additionally, one study showed the thinning of the RNFL superotemporally by 1.5 µm with an increase in the apnea-hypopnea index by 5 events per hour [ 19 ]. Several studies have described the occurrence of OSA in patients with glaucoma [ 12 , 20 , 21 , 22 ]. One study demonstrated that patients with severe OSA had >8 times RNFL thickness progression than patients with none or mild OSA [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, one study showed the thinning of the RNFL superotemporally by 1.5 µm with an increase in the apnea-hypopnea index by 5 events per hour [ 19 ]. Several studies have described the occurrence of OSA in patients with glaucoma [ 12 , 20 , 21 , 22 ]. One study demonstrated that patients with severe OSA had >8 times RNFL thickness progression than patients with none or mild OSA [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the optic nerve parameters in OCT, Lin et al [19], Casas et al [20], and Uslu et al [31] reported a greater excavation optic nerve head area (cup area) in OSAS patients than in controls. Kücük et al [36] showed that the lamina cribosa thickness was significantly thinner in OSAS patients than in controls.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it provides fast and non-invasive information on macula layer thickness, the peripapillary retinal nerve fiber layer (RNFL) and the optic nerve head (ONH) [17]. Some studies have already demonstrated retinal changes in OSAS patients, such as increased thickness in mildmoderate OSAS patients, a so-called inflammation, or a decrease in retinal thickness-a degenerative neurological process-in severe OSAS patients [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding optic nerve parameters in OCT, Lin et al [14], Casas et al [15], and Uslu et al [26] have reported a greater excavation optic nerve head area (cup area) in OSAS patients than in controls. Kücük et al [36] have shown that the lamina cribosa thickness was significantly thinner in OSAS patients than in controls.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it provides fast and non-invasive information of macula layer thickness, peripapillary retinal nerve fiber layer (RNFL) and the optic nerve head (ONH) [12]. Some studies have already demonstrated retinal changes in OSAS patients, such as increased thickness in mild-moderate OSAS patients, a so-called inflammation, or a decrease in retinal thickness in severe OSAS patients, a degenerative neurological process [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%